Efektivitas Konseling Kelompok Pendekatan Rational Emotif Behavior Therapy untuk Meningkatkan Efikasi Diri Siswa - Astuti, Widia; Fitriani, Wahidah (JKP (Jurnal Konseling Pendidikan), 2024)
The aim of this research is to find out how effective group counseling with the rational emotive behavior therapy (REBT) approach is in increasing student success rates. Previous studies show that students who lack self-efficacy have a tendency to cope with academic pressure, manage assignments, and are disinterested in learning. This study looks at how effective group counseling with the Rational Emotive Behavior Therapy (REBT) approach is in increasing students' self-efficiency. The results of previous research show that group counseling with RBT is very effective in increasing students' self-efficiency.